PENGARUH RASIO KEUANGAN PADA KECEPATAN PUBLIKASI LAPORAN KEUANGAN TAHUNAN - Budiadnyani, Ni Putu; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2015)
Time of financial reporting is useful for users to maximize utility. The purpose of study is to determine the effect of profitability, liquidity, solvency, and earnings per share at the speed of publication of annual financial statements. Numbers of samples analyzed are 366 samples of manufacturing companies listed on the Indonesian Stock Exchange for three years. The sampling method used nonprobability with saturated sample technique. A multiple linear regression is analysis technique. The results were the profitability has a negative effect on the time of annual financial reporting. Meanwhile liquidity, solvency and earnings per share have no significant association with the time of annual financial reporting. High and low liquidity ratios, solvency, and earnings per share doesn’t lead to faster company publishes its annual financial statements.
Keywords: profitability, liquidity, solvency, earnings per share, time of reporting